The Fire Exposure Effect on Hybrid Reinforced Reactive Powder Concrete Columns - Hasanain A. Shubbar; Nameer A. Alwash (Salehan Institute of Higher Education, 2020)
This paper offers an experimental investigation of the fiber reinforced reactive powder concrete columns' behavior after exposure to fire and improvements made to improve column resistance against fire. This study is mainly aimed to study the experimental behavior of hybrid reinforced columns produced by reactive concrete powder (RPC) and exposure to the flame of fire at one side and subjected to eccentric load. The experimental methodology consists of sixteen RC columns that organized into four groups based on the variables used in this research: (SF) steel fibers, (PP) polypropylene fibers, (HB) hybrid fibers, (PPC-SF) hybrid cross-section (steel fiber reactive powder concrete core with polypropylene fiber reactive powder concrete cover). All columns were tested under 60 mm eccentric load and the burn columns were exposed to fire for different duration (1, 1.5 and 2) hours. The results indicated that (SF-RPC, PP-RPC, HB-RPC, PPC-SFRPC) columns exposed to a fire flame for the period 2 hours, lost from their load capacity by about (54.39, 40.03, 34.69 and 30.68) % respectively. The main conclusion of this paper is that the best fire resistance of the column obtained when using a hybrid cross-section (steel fiber reactive powder concrete core with polypropylene fiber reactive powder concrete cover).